Non-Lethal Blood Sampling of Fish in the lab and Field With Methods for Dried Blood Plasma Spot Omic Analyses - Pollard, S; Anderson, JC; Bah, F; Mateus, M; Sidhu, M; Simmons, DBD (Frontiers in Genetics, 2022)
There is global acknowledgment that humane methods in animal research are a priority, but few environmental effects monitoring programs use nonlethal methods for fish. The goal of the present study was to determine the impacts of sampling small volumes of blood in larger-bodied fish on survival and healing. In addition to evaluating survival following blood sampling, we evaluated the utility of dried blood spots as an alternative for sample processing and storage in the field. In our approach, we housed 80 rainbow trout (Oncorhynchus mykiss) in our flow-through aquatic facility. We then anaesthetized using MS-222 and sampled 1 µl/g bw of blood via puncture of the caudal vasculature. We tested four different post-blood sampling treatments on the puncture wound: 1. application of liquid bandage; 2. a swab of betadine; 3. a swab of fish mucous; and 4. compared survival outcomes to a group where no post-treatment was performed (negative control). Overall, we observed 90% survival among all treatments, with the most effective approach being the negative control (100% survival). Based upon these results, we repeated the blood sampling with no-post treatment using 20 rainbow trout (not previously tested upon) in situ using cages at a nearby creek and monitored survival for 2 weeks post sampling. The survival rate was 95% with full healing of the puncture site in all subjects. In addition to this, we tested the efficacy of dry blood spotting on proteomic, lipidomic and amino acid analysis as an alternative method for blood sampling processing and storage. It was found that dried plasma spotting using parafilm in conjunction with a modified Bligh-Dyer extraction offered the best balance for good recovery of protein, lipid & amino acids relative to wet plasma and Noviplex dried plasma spot cards. In this article, we will present the detailed results of these combined studies and describe what we have determined to be the safest non-lethal blood sampling protocol.